2021
DOI: 10.1158/1538-7445.sabcs20-gs2-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS2-06: Exploring the causal role of the human gut microbiome in breast cancer risk using mendelian randomization

Abstract: Background: Variation in the human gut microbiome may influence cancer progression and therapy response through various mechanisms including modulation of both immune and cell signalling pathways. Whilst observational epidemiological studies have provided evidence that the gut microbiome may play a role in cancer risk, such studies are prone to residual confounding, reverse causation, and other forms of bias. Therefore, the nature of these associations still remains unclear. Mendelian randomization (MR) is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…In the past, the gut microbiome has already been linked to the efficacy of immunotherapy in cancer patients [49]. The association between gut microbiome and breast cancer risk has also been studied [50] by now based on an existing large case-control study of over 130 000 breast cancer cases and more than 110 000 controls [51]. Moreover, studies were included that had investigated the correlation between genetic variants and the presence of specific microbiome patterns [52].…”
Section: Impact Of Diet and Microbiome On Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the gut microbiome has already been linked to the efficacy of immunotherapy in cancer patients [49]. The association between gut microbiome and breast cancer risk has also been studied [50] by now based on an existing large case-control study of over 130 000 breast cancer cases and more than 110 000 controls [51]. Moreover, studies were included that had investigated the correlation between genetic variants and the presence of specific microbiome patterns [52].…”
Section: Impact Of Diet and Microbiome On Breast Cancer Riskmentioning
confidence: 99%
“…In the overall population, the bacterial genus ruminococcus was identified as a risk factor. In triple-negative breast cancer (TNBC), bacteria of the genus parabacteroides have been identified as protective and unclassified bacteria of the order bacteroidales as risk factors [50]. However, as the interaction between health and the microbiome is not yet fully understood, it is difficult to establish a risk-reducing interventional strategy based on this data.…”
Section: Impact Of Diet and Microbiome On Breast Cancer Riskmentioning
confidence: 99%
“…[49]. Nun wurde auch der Zusammenhang zwischen Darmmikrobiom und Brustkrebsrisiko untersucht [50] wobei auf eine bestehende große Fallkontrollstudie mit mehr als 130 000 Brustkrebsfällen und mehr als 110 000 Kontrollen zurückgegriffen wurde [51]. Weiterhin wurden Studien berücksichtigt, welche die Assoziation von genetischen Varianten und dem Auftreten von spezifischen Mikrobiommustern untersucht hatten [52].…”
Section: Einfluss Von Ernährung Und Mikrobiom Auf Das Brustkrebsrisikounclassified
“…In der Gesamtpopulation wurden Bakterien der Art Genus Ruminococcus als Risikofaktor identifiziert. Für das triple-negative Mammakarzinom (TNBC) wurden Bakterien der Gattung G. Parabacteroides als protektiv und unklassifizierte Bacteroidales-Bakterien als Risikofaktoren identifiziert [50]. Da die Zusammenhänge zwischen Gesundheit und dem Mikrobiom noch nicht vollständig geklärt sind, ist es jedoch schwierig, eine risikoreduzierende Intervention anhand dieser Daten zu etablieren.…”
Section: Einfluss Von Ernährung Und Mikrobiom Auf Das Brustkrebsrisikounclassified
“…18 Some studies have suggested that folic acid might have a protective effect in those who consume alcohol on a regular basis 19,20 although this has not been confirmed in prospective, randomized clinical trials. There are several other areas of interest in breast cancer prevention including looking at the gut microbiome, 21 ruxolitinib in patients with premalignant breast lesions, 22 aspirin use in preventing recurrence, 23 and topical tamoxifen. 24 Some of the most interesting data from the WHI have been the studies looking at hormone replacement therapy (HRT).…”
mentioning
confidence: 99%